2016
DOI: 10.3109/14767058.2015.1124082
|View full text |Cite
|
Sign up to set email alerts
|

Increasing maternal body mass index during pregnancy increases neonatal intensive care unit admission in near and full-term infants

Abstract: This study demonstrated a significant association between higher mBMI groups and NICU admissions independent of diagnosis of maternal comorbidities. However, accounting for NH eliminating this association suggests a pre-clinical diabetic pathology in obese women that affects newborn outcome. Despite increased percentage of nonwhite mothers in higher mBMI groups, African-American race does not seem to be a significant contributing factor in the increased rate of NICU admission in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…In line with the developmental origins of health and disease hypothesis, epidemiologic studies have linked pregravid obesity with detrimental cardiometabolic, neurocognitive, and behavioral outcomes in the offspring . More recent studies have also revealed a significant impact on the fetal immune system indicated by a higher incidence of bacterial and viral infections in neonates born to mothers with obesity that require admission to the neonatal intensive care unit . Moreover, the higher incidence of pregravid obesity has been implicated in the rising prevalence of allergic diseases (childhood wheeze and atopy) and asthma during early life, childhood, and adolescence .…”
Section: Introductionmentioning
confidence: 96%
“…In line with the developmental origins of health and disease hypothesis, epidemiologic studies have linked pregravid obesity with detrimental cardiometabolic, neurocognitive, and behavioral outcomes in the offspring . More recent studies have also revealed a significant impact on the fetal immune system indicated by a higher incidence of bacterial and viral infections in neonates born to mothers with obesity that require admission to the neonatal intensive care unit . Moreover, the higher incidence of pregravid obesity has been implicated in the rising prevalence of allergic diseases (childhood wheeze and atopy) and asthma during early life, childhood, and adolescence .…”
Section: Introductionmentioning
confidence: 96%
“…Apart from the impact of maternal obesity on increasing numerous fetal and perinatal health risks, 4-7 studies also demonstrate continued long-term risks for offspring including childhood obesity, 8, 9 metabolic dysregulation, 9 asthma 2, 10 and increased inflammation. 10-12 Additionally, as defined by the 2009 Institute of Medicine (IOM) guidelines, 13 low as well as excessive gestational weight gain (EGWG) are associated with increased infant mortality, 14, 15 large for gestational age, and neonatal intensive care admissions.…”
Section: Introductionmentioning
confidence: 99%
“…For the fetus, complications include increased risk of stillbirth, abnormal growth, and cardiac or neural tube defects (1,4). Moreover, neonates born to obese mothers are at increased risk of bacterial sepsis and necrotizing enterocolitis, requiring admission to the neonatal intensive care unit (5,6). Some adverse health outcomes for the offspring persist into adulthood, including increased susceptibility to respiratory infections such as respiratory syncytial virus (7,8), asthma (9), wheezing (10), cancer (11), type 2 diabetes (12), and cardiovascular disease (13), culminating in an increased risk for all-cause offspring mortality (14).…”
mentioning
confidence: 99%